2018
DOI: 10.1186/s13028-018-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemotrophic mycoplasma in Simmental cattle in Bavaria: prevalence, blood parameters, and transplacental transmission of ‘Candidatus Mycoplasma haemobos’ and Mycoplasma wenyonii

Abstract: BackgroundThe significance of hemotrophic mycoplasma in cattle remains unclear. Especially in Europe, their epidemiological parameters as well as pathophysiological influence on cows are lacking. The objectives of this study were: (1) to describe the prevalence of ‘Candidatus Mycoplasma haemobos’ (‘C. M. haemobos’) and Mycoplasma wenyonii (M. wenyonii) in Bavaria, Germany; (2) to evaluate their association with several blood parameters; (3) to explore the potential of vertical transmission in Simmental cattle;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
(38 reference statements)
1
15
1
Order By: Relevance
“…In contrast, Niethammer et al . [ 15 ] found that 56.59% of Simmental cows were positive for CMh, while 8.54% and 4.88% were positive for Mw or mixed infections, respectively. The difference in the prevalence of the single species may be due to the difference in climate, which could favor vector-borne transmission, breed susceptibility, housing system (barn vs. pasture), or the age of animals [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, Niethammer et al . [ 15 ] found that 56.59% of Simmental cows were positive for CMh, while 8.54% and 4.88% were positive for Mw or mixed infections, respectively. The difference in the prevalence of the single species may be due to the difference in climate, which could favor vector-borne transmission, breed susceptibility, housing system (barn vs. pasture), or the age of animals [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher WBC levels in Mw-infected cattle than in CMh-infected and hemoplasma-negative cattle have been reported [ 26 ]. Additionally, higher WBC values have been found in CMh-infected and dual infected Simmental cattle [ 15 ]. The increased WBC levels observed in our study may be due to a consequence of a presumably strong stimulation of immunity by coinfection and consequently higher numbers of leukocytes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, M. wenyonii and Ca. M. haemobos have been described as major hemoplasmas that infect cattle worldwide [8][9][10]. In cattle, acute hemoplasma infections are rare but are characterized by anemia, fever, depression and diarrhea [11,12].…”
Section: Introductionmentioning
confidence: 99%